Jogo digital: aspectos psicofisiológicos no processo de imersão - Rosilane Ribeiro da Mota (2014)
Knowledge of immersion about interaction in Digital Artworks as digital games is essential for formulation and review of their production process, likewise consummation analysis of experience until its end. One way to identify information related to player immersion is using Biometric Interfaces to measure psychophysiological responses associated with player emotion fluctuations evoked by selected external stimulus. So, it was noted changes in immersion process by variations in electrodermal activity evoked with the control of visual and sound variations into first person shooter game (FPS). As study object, we opted for qualitative analysis of immersion aspects and quantitative analysis ofpsychophysiological signal fluctuation during interaction in game. Sample of population was 42 undergraduate students or professionals of Belo Horizonte undergraduation courses related direct or indirectly to games. As inclusion criteria for population sample, it was used age and education level. Data collection techniques were self-report psychological tests for constructs of empathy and impulsivity, semistructured interviews and questionnaires applied in players using Q Sensor, noninvasivepsychophysiological sensor, before and after game interaction of 10-15minutes in addition to notes and filming. This game was developed to Unity 3D for permitting to control activation and deactivation of sound and visual elements during interaction. Based on data analysis, it was possible to verify significant variations in skin electrodermal activity (EDA) to enemies attack and sound deactivation. For texture deactivation, sound or texture activation, notes were showed, although they weren´t significant. Based on questionnaire answers, interviews and player writing reports, it was verified that interventions in sound element caused greater Sympathetic Nervous System activation and deactivation than similar situations in texture element variations. About empathy and impulsivity constructs, they were measured by BIS-11 and Empathy Inventory. And it was verified that players who like FPS games have tendency to greater impulsivity than who dislike or haven´t ability.Furthermore, for the majority of players, regardless of FPS game preference level, altruism got higher levels. Postural movements and gestures were exemplified as an expression of emocional and physiological engagement in game, indicating players were in immersion process. Thus, it was concluded that immersive process of player is related to aesthetic information, analyzed by game audiovisual elements. The fact of controlled aesthetic modification had caused significant impact in psychophysiological signals determines it is necessary to make more research with other kinds of physiological signal measures about games and too to analyze other game genres. These results could be used in game development process or in other processes as therapy.